PENINGKATAN PRESTASI BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING LEARNING PADA MATERI MASA PUBERTAS DI KELAS VISD NEGERI BUKIT TIGA ACEH TIMUR - Nurul Fadillah,; Intan Rizqi, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
A teacher is able to create interactive learning using digital media, as well as as a guide, meaning directing digital devices owned by students to support learning, for example using e-learning installed from each student's smartphone. Therefore, a teacher is required to use a learning method and be able to apply this method in the learning process. The learning method is a systematic and regular process carried out by teachers or educators in conveying material to their students. Based on this, researchers are interested in using the Contextual Teaching Learning Model in thematic learning on the subject of puberty. The implementation of this class action improvement will be carried out on grade VI students at SD Negeri Bukit Tiga for the 2020/2021 academic year. With a total of 24 students, consisting of 12 female students and 12 male students. From the overall results of improvements regarding the addition of various forms of fractions in grade VI students at SD Negeri Bukit Tiga, it can be concluded that learning the Contextual Teaching Learning Model can improve student achievement in grade VI students at SD Negeri Bukit Tiga. It is known from the increase in the average value of learning outcomes from the first cycle 41.66%, the second cycle 87.5%. The increase in student scores is assumed to be the result of treatment that is given more emphasis to students by using media in learning mathematics in everyday life